Feasibility of running a micro gas turbine on wood-derived fast pyrolysis bio-oils: Effect of the fuel spray formation and preparation. (November 2021) - Broumand, Mohsen; Khan, Muhammad Shahzeb; Yun, Sean; Hong, Zekai; Thomson, Murray J.
Abstract: This study examines the feasibility of using fast pyrolysis bio-oil (FPBO) made from non-food woody biomass in a micro-gas turbine with a unique burner design, motivated by the recent surge in the development of renewable carbon-neutral biomass-derived liquids in energy applications. The study is comprehensive and covers FPBO production and applications, physicochemical properties and spray characteristics, and combustion performance. The effects of fuel spray formation and preparation on the combustion of FPBO, ethanol (EtOH) and diesel fuel were investigated using two twin-fluid nozzles with distinct atomization mechanisms, externally- and internally-mixed, and a premixer tube. In contrast to diesel fuel and EtOH, reaching a stable flame using 100% FPBO was impossible because of the fuel polymerization (or coking) when impinging on the high-temperature inner wall of the premixer tube. EtOH addition was, therefore, used to address the problem by improving the FPBO's volatility. The FPBO spray flame generated by the internally-mixed nozzle exhibited less gas- and solid-phase emissions than the externally-mixed one and required less EtOH addition for stabilization. While this study shows the feasibility for deployment of FPBO in the present micro-gas turbine design, injector modification or fuel upgrading are necessary prior to it being used to replace fossil oils. Highlights: Spray combustion and emissions of FPBO in a micro gas turbine burner were studied. Two twin-fluid nozzles with distinct atomization mechanisms were compared. EtOH addition reduced the FPBO coking propensity consistent with its TGA residue. FPBO gas- and solid-phase emissions were reduced using an internally-mixed nozzle. Suggestions for the future deployment of biomass-derived liquids are presented.